Redesigning the interior of the Gedhong Karya Baksana kitchen at the Surakarta Kasunanan Palace using revitalization as an approach - Purnomo, Agung; Sumarno, Sumarno; Kurniawan, Donie Fadjar; Badriyah, Siti; Hapsari, Putri Sekar (International Journal of Visual and Performing Arts, 2025)
The Gedhong Karya Baksana kitchen at the Surakarta Kasunanan Palace holds a vital function in serving meals for palace members and guests, reflecting both social and cultural values within the royal environment. However, its functional role has gradually declined due to the absence of spatial efficiency and modernization in supporting large-scale banquet activities. This study aims to redesign the interior of the Gedhong Karya Baksana kitchen by applying revitalization as an approach to enhance its usability while preserving its historical and aesthetic identity. The research adopts a qualitative method with a cyclical and linear design process characteristic of action research, enabling continuous evaluation throughout the design stages. Data were collected through observation, in-depth interviews, and documentation to capture spatial conditions, user behavior, and cultural context. The collected data were then classified, analyzed, and interpreted to identify design problems and opportunities for spatial improvement. The redesign outcomes emphasize the creation of an efficient and adaptive kitchen layout that integrates modern functionality with traditional visual elements. This study demonstrates that revitalization can serve as a sustainable design strategy for historical interiors, ensuring that modernization efforts remain respectful to cultural authenticity. The redesigned kitchen not only restores the building’s functional role but also encourages the palace management to revive adaptive and environmentally conscious culinary practices that align with contemporary needs.